Determining the effectiveness of adult measures of standardised age estimation on juveniles in a Western Australian population. Issue 4 (4th July 2017) - Marroquin, T.Y.; Karkhanis, S.; Kvaal, S.I.; Vasudavan, S.; Castelblanco, E.; Kruger, E.; Tennant, M.
Abstract : The estimation of chronological age through assessment of dental radiographs is well-established and a useful method to assist in the identification of persons in forensic and anthropological scenarios. The objective of our investigation was twofold: (i) to validate the Kvaal et al. age-estimation method on a sample of Western Australian subjects, and (ii) to increase the range of chronological ages to which the Kvaal et al. method can be applied. Our sample size included panoramic radiographs from 74 subjects (aged 12–28 years). A set of ratios were calculated and then used to apply different statistical models of linear regression, in order to generate a final formula to estimate age. The most accurate estimations were obtained from the models generated by the mandibular canine measurement (SEE ± 3.708 years), and for the three mandibular teeth (SEE ± 3.388 years). The results indicate that inclusion of juveniles did not affect final results, and the method still produced estimates acceptable in a forensic framework.